Pengaruh Kepuasan Kerja dan Komitmen Organisasi Terhadap Kinerja Karyawan Pada PT Indotama Perkasa di Jakarta - Hendra, Hendra; Andi, Dede; Safiih, Abdul Rahman; Nuraldy, Hafis Laksmana; Prasetiyani, Desi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
This study aims to determine the effect of job satisfaction and organizational commitment on employee performance at PT. Indotama Perkasa in Jakarta. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study, job satisfaction has a significant effect on employee performance by 52.7%, the hypothesis test obtained t count> t table or (7,457> 2,009). Organizational commitment has a significant effect on employee performance by 46.3%, hypothesis testing is obtained t count> t table or (6,569> 2,009). Job satisfaction and organizational commitment simultaneously have a significant effect on employee performance with the regression equation Y = 8,539 + 0,399X1 + 0,393X2 and the influence contribution is 62,8%, hypothesis testing obtained F count> F table or (41,365> 2,790).